(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with increased prevalence in recent years. One of the extra skeletal functions of vitamin D is involved in regulation of immune response. Objectives: This study was to determine vitamin D status in SLE patients and the relationship with disease activity. Methods: This prospective observational study was conducted at Medicine department in Dhaka Medical College and Hospital. Data regarding disease activity of SLE was taken from 50 SLE patients fulfilling ACR criteria and disease activity was calculated by SLEDAI score. Vitamin D level was quantified by ELISA. Results: Out of 50 patients, 46(92%) were female and 4(8%) were male. Age range was 15 to 65 years and mean age was 28.00 ± 13.34 SD. Most of the population reside in rural areas (n=32, 64%) and rest from urban areas (n=18,36%). Common presentations were fever (62%), proteinuria (50%), rash (40%), vasculitis (36%) and hematuria (34%). Overall mean SLEDAI score was 18.24 ± 9.67. Among the study population, 21(42%) patients had very highly active disease, 12(24%) patients had highly active disease, 11(22%) patients had moderately active disease and 6(12%) patients had mildly active disease. Mean vitamin D level was 16.70 ± 8.83 ng/ml. In this study, majority were found to be vitamin D deficient 37(74%), out of rest 7(14%) patients had insufficient vitamin D level and 6(12%) patients had sufficient vitamin D. This study showed that there is negative linear correlation between SLEDAI score and vitamin D level which is statistically significant (p value <0.001 and r=-0.577). Conclusion: Low vitamin D level in SLE patients correlated with increased disease activity. J Bangladesh Coll Phys Surg 2022; 40: 105-110